2020
DOI: 10.1016/j.celrep.2019.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Controls Cell Stemness in Acute Myeloid Leukemia and in Normal Bone Marrow

Abstract: Vitamin D (VD) is a known differentiating agent, but the role of VD receptor (VDR) is still incompletely described in acute myeloid leukemia (AML), whose treatment is based mostly on antimitotic chemotherapy. Here, we present an unexpected role of VDR in normal hematopoiesis and in leukemogenesis. Limited VDR expression is associated with impaired myeloid progenitor differentiation and is a new prognostic factor in AML. In mice, the lack of Vdr results in increased numbers of hematopoietic and leukemia stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 59 publications
0
30
0
1
Order By: Relevance
“…Clearly, any evidence for ATRA-reversible deregulation of retinoid signaling in other settings than APL could have considerable impact for patient care. Interestingly, some related findings were recently reported with vitD3 and its receptor [173]. Thus, links between nuclear receptor signaling and cancer is likely to be broader than the narrow example of APL and related APL-like diseases.…”
Section: Conclusion: Deregulated Retinoic Acid Signaling In Other Mamentioning
confidence: 74%
“…Clearly, any evidence for ATRA-reversible deregulation of retinoid signaling in other settings than APL could have considerable impact for patient care. Interestingly, some related findings were recently reported with vitD3 and its receptor [173]. Thus, links between nuclear receptor signaling and cancer is likely to be broader than the narrow example of APL and related APL-like diseases.…”
Section: Conclusion: Deregulated Retinoic Acid Signaling In Other Mamentioning
confidence: 74%
“…Our finding is consistent with recent publication from Paubelle et al that VDR is important for myeloid progenitor differentiation and is a prognostic factor in AML. Further, mice with deficient VDR have increased numbers of hematopoietic and leukemia stem cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The problem of the silencing of VDR gene expression has been addressed by the others with regard to blood cells. This year, a paper was published, which reported that VDR expression is partially regulated by methylation, and that combined hypomethylating drugs and VDR agonists synergistically induced AML cells' differentiation [32]. In this paper, the authors have presented their retrospective analysis of the AML cells from the GEO: GSE18700 study available in GenBank, which indicated that the promoter region of VDR in these cells was methylated.…”
Section: Discussionmentioning
confidence: 99%